Designing and Implementing a System to Monitor the Air Quality of Abbottabad City - Hamza, Muhammad Ameer; Ullah, Mian Raheem; Ullah, Fawad; Aslam, Muhammad Tahir; Shah, Junaid; Usama, Muhammad; Khan, Farhad (Iraqi Journal of Civil Engineering, 2025)
This research investigates air quality and environmental conditions at COMSATS University Islamabad Abbottabad Campus and Missile Chock using IoT-based sensors. Sensors were deployed at both sites to monitor PM 2.5 levels, AQI, temperature, humidity, and gas concentrations. Data was collected over specific intervals and analyzed to identify trends and differences. The methodology involved using IoT-based sensors to capture real-time data on environmental parameters and air quality indicators at both locations, i.e., COMSATS University and Missile Chowk. At COMSATS University, PM 2.5 levels consistently fell within the "Good" category, with readings ranging from 11 to 35 µg/m³. AQI values improved over time, dropping from 91 to 2, indicating effective air quality management. Temperature and humidity remained stable, ranging from 19°C to 21.4°C and 57% to 63%, respectively. The MQ-2 sensor said that the gas levels were between 2550 and 3776 parts per million. On the other hand, Missile Chock had higher PM 2.5 levels, which varied from "Moderate" to "Poor," with values between 11 and 139 µg/m³. Initially, the AQI measurements revealed "Moderate" pollution, but with time, they became better and reached "Good." The humidity was between 18% and 20%, while the temperature was between 30°C and 31.5°C. The MQ-2 sensor results showed that the gas levels were generally high, between 3887 and 4159 ppm. The survey shows that major cities like Missile Chock have greater pollution because of people and automobiles. On the other hand, green locations like COMSATS University have cleaner air. We need to always be aware of air pollution and do something about it so that the air quality in cities improves and the health hazards that come with it decrease.